The yoga of parenting : ten yoga-based practices to help you stay grounded, connect with your kids & be kind to yourself - Ezrin, Sarah (Shambhala, 2023)
"Bring the wisdom of yoga into your parenting journey with 34 practices to find more presence, patience, and acceptance-with your child and with yourself"--